Characterizing vibration responses of a handheld workpiece and the hand–arm system. Issue 2 (June 2021) - Xu, Xueyan S; Welcome, Daniel E; McDowell, Thomas W; Warren, Christopher; Lin, Hansheng; Xiao, Bin; Chen, Qingsong; Dong, Ren G
The objective of this study is to characterize the vibration responses of a handheld workpiece and the hand–arm system, which is an important step toward identifying and developing effective methods and technologies for controlling the vibration exposures to workers performing the grinding of handheld workpieces. This study established a method for measuring the vibration responses of the entire workpiece–hand–arm system; the vibration exposure of a worker holding and pressing a typical workpiece against a sanding belt or grinding wheel in order to shape the workpiece was simulated. This method was applied to measure the apparent mass and vibration transmissibility of the system under two different feed forces (15 N and 30 N) and six simulated grinding interfaces with different stiffness values. A major resonance was observed in each transmissibility spectrum of the workpiece, which was correlated with the major resonance of the impedance of the entire system. This resonant frequency depended primarily on the workpiece mass and the grinding interface stiffness, but the hand–arm system could substantially affect the resonance magnitude. The feed force also significantly affected the resonance frequency and magnitude. While increasing the feed force increased the overall vibration transmissibility on the hand–arm system, the transmissibility with respect to the workpiece was not significantly affected by the interface conditions. The implications of the results are discussed.